1997
DOI: 10.1152/ajpheart.1997.273.5.h2333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term food restriction on cardiac mechanics

Abstract: . Effect of long-term food restriction on cardiac mechanics. Am. J. Physiol. 273 (Heart Circ. Physiol. 42): H2333-H2342, 1997.-Food restriction (FR) is the only known intervention capable of increasing mammalian life span. It not only increases longevity, but reduces the incidence of a broad spectrum of age-related pathologies, including cardiomyopathy, and retards the physiological decline associated with aging. Previous work from this laboratory has shown that long-term FR affects the contractile machinery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
(54 reference statements)
2
18
1
1
Order By: Relevance
“…Parameters assessed to evaluate systolic function are those most commonly utilized in this preparation (6,21,38,43,46): 1) slope of end-systolic pressure-volume normalized relationship (ESPVNR; mmHg ⅐ ml Ϫ1 ⅐ g Ϫ1 ) [volume was normalized to LVW as suggested by Suga et al (44) and the mean ESPVNR curve was obtained; steeper slope indicates increased myocardial contractility]; 2) maximum rate of ventricular pressure rise (ϩdP/dt; mmHg/s); and 3) maximum developed pressure (DP max; mmHg), corresponding to the difference between peak systolic pressure and diastolic pressure with the LV balloon filled to develop an end-diastolic pressure of 25 mmHg.…”
Section: Systolic Function Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters assessed to evaluate systolic function are those most commonly utilized in this preparation (6,21,38,43,46): 1) slope of end-systolic pressure-volume normalized relationship (ESPVNR; mmHg ⅐ ml Ϫ1 ⅐ g Ϫ1 ) [volume was normalized to LVW as suggested by Suga et al (44) and the mean ESPVNR curve was obtained; steeper slope indicates increased myocardial contractility]; 2) maximum rate of ventricular pressure rise (ϩdP/dt; mmHg/s); and 3) maximum developed pressure (DP max; mmHg), corresponding to the difference between peak systolic pressure and diastolic pressure with the LV balloon filled to develop an end-diastolic pressure of 25 mmHg.…”
Section: Systolic Function Indexesmentioning
confidence: 99%
“…Various studies have separately assessed passive properties of cardiac muscle (30) and the LV chamber (2, 3), as well as the active relaxation phase (19,21,39); however, none has evaluated all these indexes in the same animal model as was done in this study.…”
mentioning
confidence: 99%
“…During postnatal development the contractile apparatus matures (12) and this is associated with profound changes in the modulatory effect of b-adrenoreceptor signalling. Novotny et al (13) suggested that the differential maturation of various components of the signal transduction pathway may contribute to complex age-dependent changes in the cardiac responsiveness and sensitivity to b-adrenergic stimulation.It is well established that food restriction of the adult rat modifies b-adrenergic responsiveness of the heart (14,15) , suggesting that these pathways are responsive to nutritional * Corresponding author: Dr Matthew Elmes, fax þ44 115 951 6122, email matthew.elmes@nottingham.ac.uk Abbreviations: AUC, area under the curve; dP/dt max , rate of pressure development; LVDP, left ventricular developed pressure; MLP, maternal low protein. …”
mentioning
confidence: 99%
“…It is well established that food restriction of the adult rat modifies b-adrenergic responsiveness of the heart (14,15) , suggesting that these pathways are responsive to nutritional * Corresponding author: Dr Matthew Elmes, fax þ44 115 951 6122, email matthew.elmes@nottingham.ac.uk Abbreviations: AUC, area under the curve; dP/dt max , rate of pressure development; LVDP, left ventricular developed pressure; MLP, maternal low protein.…”
mentioning
confidence: 99%
“…This period of time was chosen because Klebanov et al 10 observed similar changes in mechanical function of normotensive rats when undergoing FR for 10 to 13 months or for three weeks. The hypothesis tested was that hypertrophied hearts, which need a higher nutritional supply, would present more changes with FR.…”
mentioning
confidence: 99%